Politics, poetry, and sufism in medieval Iran : new perspectives on Jami's Salaman va Absal - Lingwood, Chad G. (Studies in Persian Cultural History, 2013)
In Politics, Poetry, and Sufism in Medieval Iran Chad Lingwood offers new insights into the political significance of poetry and Sufism at the court of Sulṭān Ya'qūb (d. 896/1490), leader of the Āq Qoyūnlū. The basis of the study is Salāmān va Absāl , a Persian allegorical romance 'Abd al-Raḥmān Jāmī (d. 898/1492), the great Timurid belletrist and Naqshbandi Sufi, dedicated to Ya'qūb. Lingwood demonstrates that Salāmān va Absāl , which modern critics have dismissed as 'crude' and 'grotesque,' is a sophisticated work of political and mystical advice for a Muslim ruler. In the process, he challenges received wisdom concerning Jāmī, the Āq Qoyūnlū, and Perso-Islamic advice literature. Significantly, the study illustrates the extent to which Jāmī's compositions integrated the Timurid and Āq Qoyūnlū realms.